Experiential Marketing: Bibliometric Mapping of Consumer Engagement - Frans Sudirjo; Rival Pahrijal; Rani Eka Arini (West Science Social and Humanities Studies, 2025)
This research explores the intellectual landscape and dynamic themes of consumer engagement with experiential marketing by undertaking a bibliometric analysis. The research, which has spanned more than two decades of research literature on Scopus, has identified the emerging trends, themes, and influential research works, thus presenting a broad picture of this area of research focus. The research results make it clear that there is an increasingly important role of immersive technologies such as Augmented Reality (AR) and Virtual Reality (VR), social media, and other related elements that help intensify consumer engagement practices. The research work proposes a decision-making model regarding customer engagement strategy and delves into the interdisciplinary aspects of this research area, which encompasses psychology, digital media, and marketing strategy. The research work, while presenting its findings, also brings into focus the scattered nature of research work and the need to further investigate new trends and cross-discipline perspectives related to the global scenario of consumer engagement research.